Do submerged macrophyte species influence crustacean zooplankton functional group richness and their resource use efficiency in the low-light environment? - Wang, Li; Ma, Xufa; Chen, Jun (Frontiers in Plant Science, 2023)
As high grazing of epiphytic zooplankton in submerged macrophyte beds, the changes in crustacean zooplankton functional group are crucial for stabilizing a clear water state in shallow lakes. However, submerged macrophytes often experience low-light stress due to many ecological processes. It is unclear whether submerged macrophytes alter zooplankton functional group and their resource use efficiency under the low-light environment. We conducted two mesocosm experiments involving the treatments of low-light and submerged macrophyte species (Vallisneria natans and Potamogeton maackianus). The result showed that abiotic factors (e.g., light) were the most important driver explaining the change of zooplankton community. Specifically, zooplankton functional group (i.e., pelagic species, plant-associated species and substrate scrapers) richness and zooplankton species diversity decreased with the decreasing light intensity, especially for low substrate scrapers abundance. In addition, structural equation models showed that low-light stress decreased zooplankton resource use efficiency through decreasing zooplankton functional group richness and species diversity. And compared to species diversity, zooplankton functional group richness had greater influence on their resource use efficiency (Zp/Chl-a) under the low-light environment. Our results suggested that the low-light stress decreased zooplankton resource use efficiency through changing their functional group richness. Besides, the abundance of substrate scrapers shaked from V. natans was higher than from P. maackianus. Therefore, submerged macrophyte species influence crustacean zooplankton functional group richness and their resource use efficiency under the low-light environment. Selecting proper aquatic plants species to assure high diversity of zooplankton should be considered when conducting lake restoration by submerged macrophytes.